Implementing the Learning from the Mindfulness-based Social Work and Self-care Programme to Social Work Student Practice during COVID-19: A Qualitative Study. (13th May 2022) - Maddock, Alan; McCusker, Pearse
Abstract: This is the first study which has explored how social work students have applied the learning from a bespoke Mindfulness-Based Social Work and Self-Care (MBSWSC) programme to their social work practice. A qualitative research design was chosen, and a realist ontological position taken. The qualitative data were collected from reflective journals from seven social work students on placement who had completed the MBSWSC programme. An inductive thematic and comparative analysis methodology was used to identify key themes. This study found that the MBSWSC programme supported students to cope with the stress and anxiety that manifested before and during their placement. Students highlighted how switching from an avoidant to an approach oriented coping strategy allowed them to alleviate any negative thoughts or feelings they were experiencing. Students identified that this allowed them to employ more positive responses when dealing with stress. Students outlined that the learning from the programme allowed them to develop increased self-awareness, empathy, reflection and reflexivity skills, all of which will likely enhance their capacity for anti-oppressive social work practice. It is clear that improved access to the MBSWSC programme will allow social work students to develop the skills necessary to practice sustainably over the longer term. Abstract : There has been very little social work research which has focussed on how mindfulness training might help student social workers to develop key social work skills and abilities. This is the first study which explored how social work students applied the self-care and approach stress coping skills they learned as part of a six-week mindfulness programme, which was developed specifically for social workers and social work students, to their social work practice. This study analysed the reflective journal entries of seven students who had just completed this mindfulness programme and were currently on their student social work practice placement. This study found that students felt better able to manage stress and feelings of anxiety when they occurred during their social work practice. Students also felt that they also developed key social work skills and values, including self-awareness, empathy and reflection skills, all of which will improve their ability to support service users effectively. Increased access to the Mindfulness-Based Social Work and Self-Care programme is thus likely to allow social work students to be able to practice in a sustainable way in the longer term, within a profession which has high rates of burnout and attrition.